YIA2 11β-HSD1 deficiency attenuates atherosclerosis in ApoE−/− mice: role of both glucocorticoid and non-glucocorticoid (oxysterol) factors. Issue 17 (26th August 2010) - Mitic, T; Hadoke, P W F; Chuaiphichai, S; Man, T Y; Miller, E; Andrew, R; Walker, B R; Chapman, K E; Seckl, J R
Abstract : 11β-Hydroxysteroid dehydrogenase type 1 (11β-HSD1) regenerates active glucocorticoids, amplifying intracellular actions.1 11β-HSD1 deficiency or inhibition improves metabolic syndrome and attenuates atherosclerosis in vulnerable rodent strains and is a target for drug development.2–4 However, 11β-HSD1 also catalyses conversion of 7-ketocholesterol, 5 which accumulates in fatty tissues, 6 to potentially more atherogenic 7β-hydroxycholesterol. Whether atheroprotection with 11β-HSD1 deficiency is dependent on glucocorticoid or oxysterol effects is unknown. Male atherosclerosis-prone ApoE−/− and ApoE−/−.11β-HSD1−/− double knockout (DKO) mice underwent adrenalectomy or sham surgery (n=8/group), then received a high (0.2%) cholesterol Western diet for 12 weeks. The aorta and branches were perfusion-fixed. Lesion volume and extracellular lipids were determined by 3D optical projection tomography. Data are mean±SE of the means. Adrenalectomy had no effect on body/organ weights in either genotype. Removal of endogenous glucocorticoids by adrenalectomy in ApoE−/− mice did not reduce lesion volume (232±24 vs 235±34 μm 3 sham control). DKO mice had reduced lesion volumes (139±17 μm 3 ) compared with ApoE−/−(p<0.05). Adrenalectomy reversed this effect (263±52 μm 3 ). Adrenalectomised DKO mice had increased extracellular lipids (73.6±2.6 μm 3 ) within the lesion compared with either ApoE−/− adrenalectomised (37.4±5.2 μm 3 ), ApoE−/− sham (42.9±5.5 μm 3 ) or DKO sham (44.2±12 μm 3 ) group. Thus circulating glucocorticoids are necessary for 11β-HSD1 deficiency to attenuate atherosclerosis. However, 11β-HSD1 deficiency increases the lipid content of plaques in the absence of glucocorticoids, perhaps owing to accumulation of 7-ketocholesterol? Consequently, both reactions of 11β-HSD1 may be involved in the effects of the enzyme on atherogenesis.